2011
DOI: 10.1115/1.4003430
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Approach to Ballistic Dispersion of Projectile Weapons Based on Variant Launch Velocity

Abstract: This study quantifies the contribution of variant projectile velocity at a gun muzzle to its dispersion at an aim point from an analytical approach. The dispersion was formulated on the basis of stochastic physical conditions including potential crosswind effect. As a result, the statistical quantities of projectile impact distribution could be obtained from the stochastic formulation. In addition, this research proposes correction factors that may be needed when comparing dispersion in angular mil at multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Also, by analyzing data from the test firing, it is possible to identify almost all disturbances leading to the final dispersionfor example, parameters related to aging barrel, inconsistent propellant or variable atmospheric conditions. But even when such an extensive analysis is completed, a certain part of dispersion remains unexplained [6]. This part of dispersion can be largely attributed to manufacturing errors, as the following analysis will show.…”
Section: Definition Of a Problemmentioning
confidence: 97%
“…Also, by analyzing data from the test firing, it is possible to identify almost all disturbances leading to the final dispersionfor example, parameters related to aging barrel, inconsistent propellant or variable atmospheric conditions. But even when such an extensive analysis is completed, a certain part of dispersion remains unexplained [6]. This part of dispersion can be largely attributed to manufacturing errors, as the following analysis will show.…”
Section: Definition Of a Problemmentioning
confidence: 97%
“…An analytical method has been applied to determine the effect of muzzle velocity variations on the dispersion taking into account the air drag, gravity drop and crosswind 26 . It was found that the muzzle velocity variation, in combination with gravity effect, becomes a significant parameter in determining dispersion in the elevation direction.…”
Section: Introductionmentioning
confidence: 99%
“…The first analytical solution to point-mass differential equations was obtained by Johann Bernoulli in 1711 [18]. The Tank Accuracy Model (TAM) is one such point mass direct fire model that represents the theory of tank gun accuracy and was based on the AMSAA PH1 program [16], [19], [20]. It can simulate firing situations for an M1 tank by reading ballistic, fire control, and atmospheric data as well as various error inputs.…”
Section: Tank Accuracy Model (Tam) Overviewmentioning
confidence: 99%